Videojuegos y cambio climático: diseño de un living lab para la cocreación entre arte y ciencia - Dra. Maria Josep PICÓ,Dr. Esteban GALÁN-CUBILLO,Dr. Emilio SÁEZ-SORO (Fonseca, Journal of Communication, 2023)
Videogames have become a highly effective tool for the creation of contemporary cultural products and for the promotion of synergies between disciplines such as art, audiovisual and scientific dissemination. This article presents the outcomes from the Living Lab Planeta Debug, backed by an interdisciplinary team, with the purpose of innovating the research processes that address the challenge of climate change and global sustainability through video games and gamification.